To Value or Not to Value the Arctic Winter Games? - Mahadevan, Renuka; Ren, Carina Bregnholm (Event Management, 2019)
This article examines the question of how to engage with the value generated by large sport events by reviewing valuation studies on sports events and explaining the need to differentiate the valuing of events in the short and long run. It is argued that the latter, measured by the notion of public value, is a relevant concept to consider in addition to social valuation defined here as a short-run concept. The Arctic Winter Games, a youth sports event, was used to shed light on these valuation concepts by showcasing how the event spurred a large range of outcomes. Based on fieldwork in the preparation phases of the event to identify relevant outcomes and using the contingent valuation method, it was found that the social value of the Games (although it was free to attend), estimated at US$10.5 million in the short run, outweighed the cost of US$9.4 million. Some suggestions for measuring the public value of sports events and a dynamic approach of sequentially refining the process of exploring and measuring long-lasting effects as they vanish or unfold is proposed.